N-Heterocyclic carbene-mediated reactions : controlling the fate of the Breslow Intermediate - Fagan, Claire-Louise (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
We have developed a highly efficient, broad scope, additive-free mild protocol for the oxidative carbene-catalysed esterification of aldehydes. We have unambiguously identified benzoin as the oxidised species in these aerobic NHC-catalysed aldehyde esterifications proving that these reactions are mechanistically distinct from previously reported, similar esterifications. We also reported the first carbene-catalysed aerobic oxidative cleavage of cyclic 1,2-diketones and consequently exploited this novel organocatalytic process using similar reaction conditions to allow for the one-pot synthesis of an anhydride.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin